In vitro fermentability of a broad range of natural ingredients by fecal microbiota from lean and obese individuals: potential health benefits. (17th February 2022) - Gual-Grau, Andreu; Guirro, Maria; Crescenti, Anna; Boqué, Noemí; Arola, Lluís
Abstract: The prevalence of obesity and related complications is continuously increasing while the gut microbiota might have a significant role to address this challenge. In this context, the food industry generates large amounts of residues that could be likely revalorised as functional ingredients. Hence, we evaluated the fermentability of food skins, husks, shells, trimming residues, mosses and mushrooms, which were subjected to in vitro fermentation with faecal microbiota from lean and obese adults. We demonstrated for the first time that pumpkin skin is highly fermented by human faecal microbiota showing pH-lowering effects and promoting gas and SCFA production. Furthermore, brewers' spent grain generated an inulin-like SCFA profile after microbial fermentation, whereas Irish moss, plum skin, quinoa husk and mushrooms, including Armillaria mellea and Boletus edulis, showed high fermentation rates. Remarkably, although propionate production was significantly higher in obese individuals, the fermentability of the ingredients was similar between lean and obese conditions.